Atypical eclampsia: A case report - Sriyanti, Roza; Aldhi, Aldhi; Permatasari, Ressy (Fakultas Kedokteran Universitas Andalas, 2022)
Background: Most women with eclampsia have a previous history of preeclampsia (proteinuria and hypertension). However, there has been a paradigm shift in this philosophy. There is evidence that atypical eclampsia can occur even in the absence of proteinuria and hypertension which presents a diagnostic dilemma and challenge for obstetricians and gynecologists. The purpose of this case report is to raise awareness about nonclassical and atypical signs of eclampsia so as to avoid complications Case: A multigravida woman with 39-40 weeks gestational age came to the hospital with signs of labor. On examination, blood pressure was 120/70 mmHg without a history of hypertension during antenatal examination, fetal heart rate was 146-156 beats/minute, cervical dilatation was 7-8 cm, with routine blood results within normal limits and planned for vaginal delivery . When monitoring the patient suddenly had a tonic clonic seizure, a complete blood count was performed, liver, kidney, electrolyte function was within normal limits, and proteinuria was found to be +2. The patient was treated with magnesium sulfate and the baby was delivered by vacuum extraction. This patient was managed appropriately with good outcome Discussion: Atypical eclampsia accounts for about 8% of all cases of eclampsia. Atypical forms of eclampsia have an erratic onset. This experience highlights some of the difficulties in managing atypical cases of eclampsia, namely the erratic onset and unpredictable course of the disease that can interfere with timely diagnosis and treatment and contribute to maternal and fetal morbidity and mortality. While controlling seizures by initiating magnesium sulfate therapy,